Exploring the use of WeChat for qualitative social research: The case of Italian digital diaspora in Shanghai - Moffa, Grazia; Di Gregorio, Marco (Frontiers in Sociology, 2023)
The widespread use of digital communication technologies has created new opportunities for social research. In this paper, we explore the limits and potentials of using messaging and social media apps as tools for qualitative research. Building upon our research on Italian migration to Shanghai, we discuss in detail the methodological choice of using WeChat for teamwork, remote sampling strategies, and conducting interviews. The paper highlights the benefits that researchers may have from employing the same technology that the studied community uses in their daily life as a research tool, and advocates for a flexible approach to research that adapts its tools and methods to the specific requirements and characteristics of the fieldwork. In our case, this strategy allowed us to emphasize that WeChat represents a digital migratory space which played a crucial role in understanding and making of the Italian digital diaspora in China.